Styl i stylizacja językowa według Krystyny Pisarkowej - SZCZERBOWSKI, TADEUSZ (Stylistyka, 2024)
Krystyna Pisarkowa expressed her academic interest in stylistics directly or indirectly in the titles of her numerous publications. Her merit is drawing attention to the treatment of the word style in colloquial language as an evaluating predicate (for example, in great/grand/fine, etc. style). In turn, she called Umberto Eco’s book, “The Name of the Rose”, a novel about the truth of signs. Krystyna Pisarkowa considered deviations from language norms and semantic shifts to be a creative way of searching for truth in signs themselves. Archaisation in Sławomir Mrożek’s work is – in her opinion – “a deliberate anachronism, a dissonance, a deformation of uses and meanings, which exposes untruth, the falsity of characters, the ugliness of banality, the ridiculousness and deadness of a pattern and template.” In her publications, she emphasised that “intention is the core of every act of communication, hence it should be discovered and that suffices.” Krystyna Pisarkowa’s research combines pragmatics with style. Her works are an invaluable lesson in style and interpretation